A kind of impact-resistant polyurethane material and preparation method thereof
Through cross-linking curing technology of modified polyurethane, modified silica nanosheets and bismaleimide, the defects of polyurethane materials in impact and combustion are solved, and the impact resistance, flame retardant and self-repair performance are improved. Suitable for construction and automotive protection fields.
Patent Information
- Application Number
- CN202411399458.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Existing polyurethane materials are prone to scratches, cracks or breaks when severely impacted, and are flammable, and do not have self-repair and flame retardant properties, which limits their application in construction, automotive protection and other fields.
Modified polyurethane, modified silica nanosheets and bismaleimide cross-linking curing technology, combined with aminopropylheptyl - Cage polysilsesquioxane end capping to form impact-resistant polyurethane materials with flame retardant, antibacterial and self-healing properties.
It improves the impact, flame retardant and antibacterial properties of the material, extends the service life, reduces maintenance costs, and realizes self-healing through dynamic reversible chemical bonds during impact, enhancing the thermal stability and corrosion resistance of the material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to an impact-resistant polyurethane material and a preparation method thereof. Background Art
[0002] As a type of polymer material, polyurethane materials are widely used in many industries due to their good mechanical properties and processing adaptability. However, existing polyurethane materials still have some limitations, which restrict their application in some fields.
[0003] For example, in the fields of construction and automobile protection, although traditional polyurethane materials have certain mechanical strength and elasticity, they are prone to scratches, cracks or breaks when subjected to severe impacts, and cannot self-repair. This not only increases maintenance costs, but may also lead to permanent degradation of material performance. Therefore, polyurethane with impact resistance can overcome this shortcoming and reduce the possibility of coating breakage under greater impact; and coatings with self-repairing properties can self-repair after scratches or cracks occur, extending the service life of the material and reducing maintenance costs;
[0004] Secondly, most polyurethane materials are easy to burn when encountering flames, releasing harmful gases, not meeting fire safety standards, and lack effective flame retardant additives or flame retardant mechanisms; it is also possible to give polyurethane materials certain flame retardant properties to improve the safety of the material during use. Summary of the invention
[0005] The purpose of the present invention is to provide an impact-resistant polyurethane material and a preparation method thereof, so as to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] The invention discloses an impact-resistant polyurethane material, which is prepared by cross-linking and curing modified polyurethane, modified silicon dioxide nanosheets and bismaleimide.
[0008] As an optimization, the modified polyurethane is a pseudo-polyrotaxane polyurethane prepared by polymerization of isophorone diisocyanate, polytetramethylene furan ether diol and pseudo-polyrotaxane, and is terminated with aminopropylheptyl-cage polysilsesquioxane.
[0009] As an optimization, the pseudopolyrotaxane is prepared by reacting polyethylene glycol and a modified pillar aromatic monomer.
[0010] As an optimization, the modified pillar aromatic monomer is obtained by reacting 1-(2-bromoethoxy)-4-methoxybenzene with p-phenylenedimethyl ether to obtain monobromoethoxy pillar aromatics, which is then reacted with (4-hydroxyphenyl)diphenylphosphine to obtain a modified pillar aromatic precursor, which is then reacted with 2-(2-bromoethyl)furan.
[0011] As an optimization, the modified silica nanosheets are obtained by reacting amino silica nanosheets with propylene oxide to obtain hydroxylated silica nanosheets to initiate the ring-opening polymerization of 6-caprolactone, and then reacting with succinic anhydride.
[0012] A method for preparing an impact-resistant polyurethane material comprises the following preparation steps:
[0013] (1) Monobromoethoxy pillar aromatic hydrocarbon, (4-hydroxyphenyl) diphenylphosphine, potassium carbonate, tetrabutylammonium bromide and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.27-0.3):(0.24-0.3):(0.03-0.05):(20-30), refluxed at 80°C for 4-6h, and the N,N-dimethylformamide is removed by vacuum rotary evaporation to obtain a modified pillar aromatic hydrocarbon precursor;
[0014] (2) uniformly mixing the modified pillar aromatic hydrocarbon precursor, 2-(2-bromoethyl) furan, triethylamine and tetrahydrofuran in a mass ratio of 1:(0.6-0.7):(0.03-0.05):(20-30), reacting at 40-50°C for 4-6h, and removing tetrahydrofuran by vacuum rotary evaporation to obtain the modified pillar aromatic hydrocarbon monomer;
[0015] (3) Mix the modified pillar aromatic monomer, polyethylene glycol and pure water in a mass ratio of 1:(0.5-0.7):(80-100), stir at 80°C for 1 hour, stirring at a speed of 500-600 r / min, cool to room temperature, continue stirring for 46-48 hours, filter and wash with pure water for 3-4 times, and dry at 100°C for 2-3 hours to obtain a pseudopolyrotaxane;
[0016] (4) At 80°C, isophorone diisocyanate, polytetramethylene glycol, pseudopolyrotaxane, dibutyltin dilaurate, and toluene are mixed in a mass ratio of 1:(2-3):(0.1-0.2):(0.03-0.05):(20-30) for 1-2 h, and n-hexane 3-4 times the volume of toluene is added, filtered, and dried at 50°C for 22-24 h to obtain a pseudopolyrotaxane polyurethane;
[0017] (5) Mixing the pseudopolyrotaxane polyurethane, aminopropylheptyl-cage polysilsesquioxane and ethanol in a mass ratio of 1:(0.5-0.7):(20-30), stirring at 80°C for 5-6 hours at a stirring speed of 300-400 r / min, adding n-hexane 3-4 times the volume of ethanol, filtering and drying at 50°C for 22-24 hours to obtain a modified polyurethane;
[0018] (6) Under nitrogen protection, polycaprolactone functionalized silica nanosheets, succinic anhydride, 4-dimethylaminopyridine, and toluene are mixed in a mass ratio of 1:(0.8-1):(0.8-1):(50-60), ultrasonicated at 40 Hz for 20 min, heated to 50-60 °C, reacted for 22-24 h, filtered, and dried at 60 °C for 6-8 h to obtain modified silica nanosheets;
[0019] (7) The modified polyurethane, modified silica nanosheets and tetrahydrofuran are mixed in a mass ratio of 1:(0.1-0.15):(30-40), and ultrasonically dispersed for 60 min. 1%-3% of bismaleimide by mass of the modified polyurethane is added, stirred for 3-5 min, poured into a polytetrafluoroethylene mold, and dried in an oven at 80°C for 48 h to obtain an impact-resistant polyurethane material.
[0020] As an optimization, the preparation method of the monobromoethoxy columnar aromatics in step (1) is as follows: 1-(2-bromoethoxy)-4-methoxybenzene and terephthalate are mixed in a molar ratio of 1:4, and then added to 1,2-dichloroethane with a mass of 50-60 times that of terephthalate; under nitrogen protection, 6 times the molar amount of paraformaldehyde is added, wherein the molar amount of paraformaldehyde refers to the molar amount of formaldehyde produced by the decomposition of paraformaldehyde; then 1.5 times the mass of 1-(2-bromoethoxy)-4-methoxy boron trifluoride ether is added; the mixture is stirred at room temperature for 3-4 hours, and 1,2-dichloroethane is removed by rotary evaporation to obtain monobromoethoxy columnar aromatics.
[0021] As an optimization, the preparation method of the polycaprolactone functionalized silica nanosheets in step (6) is as follows: at room temperature, tetraethyl orthosilicate, ethyl acetate and 0.014M sodium hydroxide solution are stirred at a volume ratio of 1:1:100 for 3-4 hours, γ-aminopropyltriethoxysilane 0.2-0.3 times the volume of tetraethyl orthosilicate is added, stirred for 5-6 hours, heated to 80-90°C for reaction for 1-2 hours, filtered and washed with pure water for 3-4 times, and dried at 50-60°C for 2-3 hours to obtain amino-functionalized silica nanosheets; under nitrogen protection, the amino The hydroxylated silica nanosheets and propylene oxide are mixed uniformly in a mass ratio of 1:(20-30), reacted at 45-50°C for 24 hours, filtered and washed with pure water, and dried at 60°C for 6-8 hours to obtain hydroxylated silica nanosheets; hydroxylated silica nanosheets, 6-caprolactone and stannous isooctanoate are mixed in a mass ratio of 1:(8-10):0.01, heated to 130°C under nitrogen protection, reacted for 5-7 hours, filtered and washed with dichloromethane for 3-4 hours, and dried at 60°C for 6-8 hours to obtain polycaprolactone functionalized silica nanosheets.
[0022] As an optimization, the molecular weight of the polyethylene glycol in step (3) is 2000.
[0023] As an optimization, the molecular weight of the polytetrahydrofuran ether diol in step (4) is 2000.
[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0025] When preparing the impact-resistant polyurethane material, the present invention firstly reacts 1-(2-bromoethoxy)-4-methoxybenzene with phenylene dimethyl ether to obtain monobromoethoxy pillar aromatics, then reacts with (4-hydroxyphenyl) diphenylphosphine to obtain a modified pillar aromatics precursor, and then reacts with 2-(2-bromoethyl) furan to obtain a modified pillar aromatics monomer; polyethylene glycol and the modified pillar aromatics monomer are reacted to obtain a pseudo-polyrotaxane; the pseudo-polyrotaxane polyurethane obtained by polymerizing isophorone diisocyanate, polytetrahydrofuran ether glycol and pseudo-polyrotaxane is capped with aminopropylheptyl-cage polysilsesquioxane and then reacted with thioglycolic acid to obtain a modified polyurethane; then, the amino-treated silicon dioxide nanosheets are reacted with glycidol to initiate the ring-opening polymerization of 6-caprolactone, and then reacted with succinic anhydride to obtain the modified silicon dioxide nanosheets; finally, the modified polyurethane, the modified silicon dioxide nanosheets and bismaleamide are mixed and cross-linked and cured to obtain the impact-resistant polyurethane material.
[0026] First, 1-(2-bromoethoxy)-4-methoxybenzene and p-phenylene dimethyl ether are reacted to form a pillar aromatic hydrocarbon containing a monobrominated functional group. The monobrominated functional group reacts with the hydroxyl group of (4-hydroxyphenyl) diphenylphosphine to graft a phosphorus element with a flame retardant function onto the pillar aromatic hydrocarbon, thereby giving the polyurethane material good flame retardancy. The monobrominated functional group reacts with the bromine on 2-(2-bromoethyl) furan to generate a modified pillar aromatic hydrocarbon monomer containing a quaternary phosphonium salt and a furanyl group. The quaternary phosphonium salt can give the polyurethane material certain antibacterial properties. The modified pillar aromatic hydrocarbon monomer is reacted with polyethylene glycol to obtain a pseudopolyrotaxane. The cavity structure inside the pillar aromatic hydrocarbon can be The quasi-polyrotaxane with polyethylene glycol as the axis and pillar aromatic hydrocarbons as the ring is formed by non-covalent action with a long chain of polyethylene glycol. The quasi-polyrotaxane is copolymerized with isophorone diisocyanate and polytetramethylene furan ether diol through hydroxyl groups at both ends to form a quasi-polyrotaxane polyurethane with isocyanate groups at both ends. The quasi-polyrotaxane polyurethane is terminated by aminopropylheptyl-cage polysilsesquioxane. The cage structure of aminopropylheptyl-cage polysilsesquioxane can provide a large steric hindrance to prevent pillar aromatic hydrocarbons from falling off the molecular chain. Siloxane structures can also be introduced at both ends of the polyurethane main chain to improve the thermal stability of the polyurethane.
[0027] Secondly, the silica nanosheets are reacted with a silane coupling agent containing an amino group to obtain an amino-modified silica nanosheet. After the surface amino group reacts with glycidol, a hydroxyl group is introduced on the surface of the silica nanosheet, and then 6-caprolactone is initiated to undergo ring-opening polymerization on the surface of the silica nanosheet. Then, succinic anhydride is used to convert the terminal hydroxyl group of polycaprolactone into a carboxyl group to obtain a modified silica nanosheet. The silica with a sheet structure dispersed in the polyurethane can prevent the corrosive medium in the air from contacting the inside of the material or the surface of the substrate coated with the polyurethane material, thereby providing a certain corrosion resistance. At the same time, the mechanical strength of the silica itself can give the polyurethane a certain impact resistance. The end of the polycaprolactone long chain generated by the polymerization of 6-caprolactone on the surface of the silica nanosheet contains a hydroxyl group, which is converted into a carboxyl group after the reaction of succinic anhydride, and can not only be electrostatically bonded with the positively charged modified polyurethane, but also make the silica nanosheets uniformly dispersed in the polyurethane to reduce agglomeration. When subjected to external force impact, the polycaprolactone organic long chain can be deformed, thereby absorbing energy and improving the impact strength.
[0028] Finally, the modified polyurethane, modified silica nanosheets and bismaleimide were blended and cross-linked and cured to obtain an impact-resistant polyurethane material. The furan group and maleimide contained on the aromatic rotaxane of the modified polyurethane main chain column underwent a Diels-Alder reaction, which not only generated dynamically reversible chemical bonds to give the polyurethane material self-healing properties, but also due to the presence of polyrotaxane, the cross-linking points generated by furanmaleimide can slide on the polyurethane main chain when impacted by external force, providing an efficient energy dissipation mechanism, dispersing the impact force and thus giving the polyurethane material impact resistance. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The molecular weight of the polyethylene glycol used in all the following examples and comparative examples is 2000; the molecular weight of the polytetrahydrofuran ether glycol is 2000. Example 1
[0031] A method for preparing an impact-resistant polyurethane material, the method comprising the following preparation steps:
[0032] (1) 1-(2-bromoethoxy)-4-methoxybenzene and terephthalate were mixed in a molar ratio of 1:4 and added to 1,2-dichloroethane with a mass of 50 times that of terephthalate. Under nitrogen protection, paraformaldehyde with a molar mass of 6 times that of 1-(2-bromoethoxy)-4-methoxybenzene was added, where the molar mass of paraformaldehyde refers to the molar mass of formaldehyde produced by the decomposition of paraformaldehyde. Then, 1-(2-bromoethoxy)-4-methoxybenzene with a mass of 1.5 times that of terephthalate was added. times of boron trifluoride etherate, stirred at room temperature for 4 hours, and 1,2-dichloroethane was removed by rotary evaporation to obtain monobromoethoxy pillar aromatics; monobromoethoxy pillar aromatics, (4-hydroxyphenyl) diphenylphosphine, potassium carbonate, tetrabutylammonium bromide and N,N-dimethylformamide were mixed in a mass ratio of 1:0.27:0.24:0.03:20, refluxed at 80°C for 6 hours, and N,N-dimethylformamide was removed by rotary evaporation under reduced pressure to obtain a modified pillar aromatics precursor;
[0033] (2) The modified pillar aromatic hydrocarbon precursor, 2-(2-bromoethyl) furan, triethylamine and tetrahydrofuran were mixed uniformly in a mass ratio of 1:0.6:0.03:20, reacted at 50°C for 6 hours, and the tetrahydrofuran was removed by vacuum rotary evaporation to obtain the modified pillar aromatic hydrocarbon monomer;
[0034] (3) The modified pillar aromatic monomer, polyethylene glycol and pure water were mixed in a mass ratio of 1:0.5:80, stirred at 80 °C for 1 h, and the stirring speed was 600 r / min. After cooling to room temperature, stirring was continued for 48 h. The mixture was filtered and washed with pure water for 4 times, and dried at 100 °C for 3 h to obtain a pseudopolyrotaxane.
[0035] (4) At 80°C, isophorone diisocyanate, polytetramethylene glycol, pseudopolyrotaxane, dibutyltin dilaurate, and toluene were mixed in a mass ratio of 1:2:0.1:0.03:20 for 2 h, and n-hexane (3 times the volume of toluene) was added. The mixture was filtered and dried at 50°C for 24 h to obtain a pseudopolyrotaxane polyurethane.
[0036] (5) The pseudopolyrotaxane polyurethane, aminopropylheptyl-cage polysilsesquioxane and ethanol were mixed in a mass ratio of 1:0.5:20, stirred at 80°C for 6 h, and a stirring speed of 400 r / min, and n-hexane 3 times the volume of ethanol was added, filtered and dried at 50°C for 24 h to obtain a modified polyurethane;
[0037] (6) Under room temperature, tetraethyl orthosilicate, ethyl acetate and 0.014M sodium hydroxide solution were stirred at a volume ratio of 1:1:100 for 4 h, γ-aminopropyltriethoxysilane (0.2 times the volume of tetraethyl orthosilicate) was added, stirred for 6 h, heated to 90°C for reaction for 2 h, filtered and washed with pure water 4 times, and dried at 60°C for 3 h to obtain amino-modified silica nanosheets; under nitrogen protection, amino-modified silica nanosheets and propylene oxide were mixed at a mass ratio of 1:20, reacted at 50°C for 24 h, filtered and washed with pure water, and dried at 60°C for 8 h to obtain hydroxylated silica nanosheets. sheet; hydroxylated silica nanosheets, 6-caprolactone and stannous isooctanoate were mixed in a mass ratio of 1:8:0.01, heated to 130°C under nitrogen protection for reaction for 7 hours, filtered and washed with dichloromethane for 4 hours, and dried at 60°C for 8 hours to obtain polycaprolactone functionalized silica nanosheets; under nitrogen protection, polycaprolactone functionalized silica nanosheets, succinic anhydride, 4-dimethylaminopyridine and toluene were mixed in a mass ratio of 1:0.8:0.8:50, ultrasonicated at 40Hz for 20 minutes, heated to 60°C, reacted for 24 hours, filtered and dried at 60°C for 8 hours to obtain modified silica nanosheets;
[0038] (7) The modified polyurethane, modified silica nanosheets and tetrahydrofuran were mixed in a mass ratio of 1:0.1:30, and ultrasonically dispersed for 60 min. 1% bismaleimide by mass of the modified polyurethane was added, stirred for 5 min, poured into a polytetrafluoroethylene mold, and dried in an oven at 80 °C for 48 h to obtain an impact-resistant polyurethane material. Example 2
[0039] A method for preparing an impact-resistant polyurethane material, the method comprising the following preparation steps:
[0040] (1) 1-(2-bromoethoxy)-4-methoxybenzene and terephthalate were mixed in a molar ratio of 1:4 and added to 1,2-dichloroethane with a mass of 55 times that of terephthalate. Under nitrogen protection, paraformaldehyde with a molar mass of 6 times that of 1-(2-bromoethoxy)-4-methoxybenzene was added, where the molar mass of paraformaldehyde refers to the molar mass of formaldehyde produced by the decomposition of paraformaldehyde. Then, 1.5 times the mass of 1-(2-bromoethoxy)-4-methoxybenzene was added. trifluoride etherate, stirred at room temperature for 3.5 hours, and 1,2-dichloroethane was removed by rotary evaporation to obtain monobromoethoxy pillar aromatics; monobromoethoxy pillar aromatics, (4-hydroxyphenyl) diphenylphosphine, potassium carbonate, tetrabutylammonium bromide and N,N-dimethylformamide were mixed in a mass ratio of 1:0.29:0.26:0.04:25, refluxed at 80°C for 5 hours, and N,N-dimethylformamide was removed by rotary evaporation under reduced pressure to obtain a modified pillar aromatics precursor;
[0041] (2) The modified pillar aromatic hydrocarbon precursor, 2-(2-bromoethyl) furan, triethylamine and tetrahydrofuran were mixed uniformly in a mass ratio of 1:0.65:0.04:25, reacted at 45°C for 5 hours, and the tetrahydrofuran was removed by vacuum rotary evaporation to obtain the modified pillar aromatic hydrocarbon monomer;
[0042] (3) The modified pillar aromatic monomer, polyethylene glycol and pure water were mixed in a mass ratio of 1:0.6:90, stirred at 80 °C for 1 h, and the stirring speed was 550 r / min. After cooling to room temperature, stirring was continued for 47 h. The mixture was filtered and washed with pure water for 3 times, and dried at 100 °C for 3 h to obtain a pseudopolyrotaxane.
[0043] (4) At 80°C, isophorone diisocyanate, polytetramethylene glycol, pseudopolyrotaxane, dibutyltin dilaurate, and toluene were mixed in a mass ratio of 1:2.5:0.15:0.04:25 for 1.5 h, and n-hexane (3.5 times the volume of toluene) was added. The mixture was filtered and dried at 50°C for 23 h to obtain a pseudopolyrotaxane polyurethane.
[0044] (5) The pseudopolyrotaxane polyurethane, aminopropylheptyl-cage polysilsesquioxane and ethanol were mixed in a mass ratio of 1:0.6:25, stirred at 80°C for 5.5 h, and a stirring speed of 350 r / min. 3.5 times the volume of ethanol was added with n-hexane, filtered and dried at 50°C for 23 h to obtain a modified polyurethane.
[0045] (6) Under room temperature, tetraethyl orthosilicate, ethyl acetate and 0.014M sodium hydroxide solution were stirred at a volume ratio of 1:1:100 for 3.5 hours, γ-aminopropyltriethoxysilane (0.25 times the volume of tetraethyl orthosilicate) was added, stirred for 5.5 hours, heated to 85°C for reaction for 1.5 hours, filtered and washed with pure water for 3 times, and dried at 55°C for 2.5 hours to obtain amino-modified silica nanosheets; under nitrogen protection, amino-modified silica nanosheets and glycidol were mixed at a mass ratio of 1:25, reacted at 47°C for 24 hours, filtered and washed with pure water, and dried at 60°C for 7 hours to obtain hydroxylated silica nanosheets. Silicon dioxide nanosheets; hydroxylated silica nanosheets, 6-caprolactone and stannous isooctanoate were mixed in a mass ratio of 1:9:0.01, heated to 130°C under nitrogen protection for reaction for 6 hours, filtered and washed with dichloromethane for 3.5 hours, and dried at 60°C for 7 hours to obtain polycaprolactone functionalized silica nanosheets; under nitrogen protection, polycaprolactone functionalized silica nanosheets, succinic anhydride, 4-dimethylaminopyridine and toluene were mixed in a mass ratio of 1:0.9:0.9:55, ultrasonicated at 40 Hz for 20 minutes, heated to 55°C, reacted for 23 hours, filtered and dried at 60°C for 7 hours to obtain modified silica nanosheets;
[0046] (7) The modified polyurethane, modified silica nanosheets and tetrahydrofuran were mixed in a mass ratio of 1:0.13:35, and ultrasonically dispersed for 60 min. 2% of bismaleimide by mass of the modified polyurethane was added, stirred for 4 min, poured into a polytetrafluoroethylene mold, and dried in an oven at 80 °C for 48 h to obtain an impact-resistant polyurethane material. Example 3
[0047] A method for preparing an impact-resistant polyurethane material, the method comprising the following preparation steps:
[0048] (1) 1-(2-bromoethoxy)-4-methoxybenzene and terephthalate were mixed in a molar ratio of 1:4 and added into 1,2-dichloroethane with a mass of 60 times that of terephthalate. Under nitrogen protection, paraformaldehyde with a molar mass of 6 times that of 1-(2-bromoethoxy)-4-methoxybenzene was added, where the molar mass of paraformaldehyde refers to the molar mass of formaldehyde generated by the decomposition of paraformaldehyde. Then, 1-(2-bromoethoxy)-4-methoxybenzene with a mass of 1. 5 times of boron trifluoride etherate, stirring at room temperature for 3 hours, and removing 1,2-dichloroethane by rotary evaporation to obtain monobromoethoxy pillar aromatics; monobromoethoxy pillar aromatics, (4-hydroxyphenyl) diphenylphosphine, potassium carbonate, tetrabutylammonium bromide and N,N-dimethylformamide are mixed in a mass ratio of 1:0.3:0.3:0.05:30, refluxed at 80°C for 4 hours, and N,N-dimethylformamide is removed by rotary evaporation under reduced pressure to obtain a modified pillar aromatics precursor;
[0049] (2) The modified pillar aromatic hydrocarbon precursor, 2-(2-bromoethyl) furan, triethylamine and tetrahydrofuran were mixed uniformly in a mass ratio of 1:0.7:0.05:30, reacted at 40°C for 4 hours, and the tetrahydrofuran was removed by vacuum rotary evaporation to obtain the modified pillar aromatic hydrocarbon monomer;
[0050] (3) The modified pillar aromatic monomer, polyethylene glycol and pure water were mixed in a mass ratio of 1:0.7:100, stirred at 80 °C for 1 h, and the stirring speed was 500 r / min. After cooling to room temperature, stirring was continued for 46 h. The mixture was filtered and washed with pure water for 3 times, and dried at 100 °C for 2 h to obtain a pseudopolyrotaxane.
[0051] (4) At 80°C, isophorone diisocyanate, polytetramethylene glycol, pseudopolyrotaxane, dibutyltin dilaurate, and toluene were mixed in a mass ratio of 1:3:0.2:0.05:30 for 1 h, and n-hexane (4 times the volume of toluene) was added, filtered, and dried at 50°C for 22 h to obtain a pseudopolyrotaxane polyurethane;
[0052] (5) The pseudopolyrotaxane polyurethane, aminopropylheptyl-cage polysilsesquioxane and ethanol were mixed in a mass ratio of 1:0.7:30, stirred at 80°C for 5 h at a stirring speed of 300 r / min, and n-hexane 4 times the volume of ethanol was added, filtered and dried at 50°C for 22 h to obtain a modified polyurethane;
[0053] (6) Under room temperature, tetraethyl orthosilicate, ethyl acetate and 0.014M sodium hydroxide solution were stirred at a volume ratio of 1:1:100 for 3 h, γ-aminopropyltriethoxysilane (0.3 times the volume of tetraethyl orthosilicate) was added, stirred for 5 h, heated to 80 °C for reaction for 1 h, filtered and washed with pure water 3 times, and dried at 50 °C for 2 h to obtain amino-containing silica nanosheets; under nitrogen protection, amino-containing silica nanosheets and propylene oxide were mixed at a mass ratio of 1:30, reacted at 45 °C for 24 h, filtered and washed with pure water, and dried at 60 °C for 6 h to obtain hydroxylated silica. Nanosheets; hydroxylated silica nanosheets, 6-caprolactone and stannous isooctanoate were mixed in a mass ratio of 1:10:0.01, heated to 130°C under nitrogen protection for reaction for 5 hours, filtered and washed with dichloromethane for 3 hours, and dried at 60°C for 6 hours to obtain polycaprolactone functionalized silica nanosheets; under nitrogen protection, polycaprolactone functionalized silica nanosheets, succinic anhydride, 4-dimethylaminopyridine and toluene were mixed in a mass ratio of 1:1:1:60, ultrasonicated at 40Hz for 20 minutes, heated to 50°C, reacted for 22 hours, filtered and dried at 60°C for 6 hours to obtain modified silica nanosheets;
[0054] (7) The modified polyurethane, modified silica nanosheets and tetrahydrofuran were mixed in a mass ratio of 1:0.15:40, and ultrasonically dispersed for 60 min. 3% of bismaleimide by mass of the modified polyurethane was added, stirred for 3 min, poured into a polytetrafluoroethylene mold, and dried in an oven at 80 °C for 48 h to obtain an impact-resistant polyurethane material.
[0055] Comparative Example 1
[0056] The preparation method of the impact-resistant polyurethane material of Comparative Example 1 differs from that of Example 2 in that steps (1), (2) and (3) are not included, and step (4) is modified as follows: at 80° C., isophorone diisocyanate, polytetramethylene furan ether glycol, dibutyltin dilaurate and toluene are mixed in a mass ratio of 1:2.5:0.15:25 for 1.5 h, 3.5 times the volume of toluene of n-hexane are added, the mixture is filtered and dried at 50° C. for 23 h to obtain a pseudopolyrotaxane polyurethane;
[0057] Comparative Example 2
[0058] The preparation method of the impact-resistant polyurethane material of Comparative Example 2 differs from that of Example 2 in that step (6) is not included, and step (7) is modified as follows: the modified polyurethane and tetrahydrofuran are mixed in a mass ratio of 1:35, ultrasonically dispersed for 60 min, 2% by mass of bismaleimide of the modified polyurethane is added, stirred for 4 min, poured into a polytetrafluoroethylene mold, and dried in an oven at 80° C. for 48 h to obtain the impact-resistant polyurethane material;
[0059] Comparative Example 3
[0060] The preparation method of the impact-resistant polyurethane material of Comparative Example 3 is different from that of Example 2 in that step (2) is not included, and step (1) is modified to: 1-(2-bromoethoxy)-4-methoxybenzene and terephthalate are mixed in a molar ratio of 1:4, and then added to 1,2-dichloroethane with a mass of 55 times that of terephthalate, and then 6 times the molar amount of 1-(2-bromoethoxy)-4-methoxybenzene is added under nitrogen protection. The molar amount of paraformaldehyde refers to the molar amount of formaldehyde generated by the decomposition of paraformaldehyde, and then 1 -(2-bromoethoxy)-4-methoxy)boron trifluoride etherate with a mass 1.5 times that of boron trifluoride, stirred at room temperature for 3.5 hours, and 1,2-dichloroethane was removed by rotary evaporation to obtain monobromoethoxy columnar aromatics; monobromoethoxy columnar aromatics, (4-hydroxyphenyl) diphenylphosphine, potassium carbonate, tetrabutylammonium bromide and N,N-dimethylformamide were mixed in a mass ratio of 1:0.29:0.26:0.04:25, refluxed at 80°C for 5 hours, and N,N-dimethylformamide was removed by rotary evaporation under reduced pressure to obtain a modified columnar aromatic monomer.
[0061] Test Example 1
[0062] Flame retardant performance test
[0063] Test method: The examples and comparative examples were prepared into samples according to the standard GB / T 2048, and the limiting oxygen index of the examples and comparative examples was tested. The results are shown in Table 1.
[0064] Table 1
[0065]
[0066] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the impact-resistant polyurethane material prepared by the present invention has good flame retardant properties.
[0067] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that first, 1-(2-bromoethoxy)-4-methoxybenzene and p-phenylenedimethyl ether are reacted to form columnar aromatics containing a monobrominated functional group, the monobrominated functional group reacts with the hydroxyl group of (4-hydroxyphenyl)diphenylphosphine, and a phosphorus element with a flame retardant function is grafted onto the columnar aromatics, thereby giving the polyurethane material good flame retardancy.
[0068] Test Example 2
[0069] Self-healing performance test
[0070] Test method: All examples and comparative examples were made into samples according to the standard GB / T 1040.3-2006, and the fracture strength of the samples was tested at a tensile rate of 50 mm / min, which was recorded as η0; the samples were cut and the cut surfaces were overlapped, and heated at 70°C for 30 minutes, and the fracture strength of the samples was tested again, which was recorded as η1. The self-healing efficiency η was calculated according to the following formula: η=(η1 / η0)*100%. The results are shown in Table 2.
[0071] Table 2
[0072]
[0073] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the impact-resistant polyurethane material prepared by the present invention has good self-repairing performance.
[0074] By comparison, the self-repairing efficiency of Examples 1 to 3 is greater than that of Comparative Examples 1 and 3, indicating that the impact-resistant polyurethane material is prepared by blending, cross-linking and curing the modified polyurethane, modified silica nanosheets and bismaleimide, and the furanyl and maleimide contained in the aromatic rotaxane of the modified polyurethane main chain column undergo Diels-Alder reaction to generate dynamic reversible chemical bonds to give the polyurethane material self-repairing properties.
[0075] Test Example 3
[0076] Impact resistance test
[0077] Test method: The impact-resistant polyurethane materials prepared in the examples and comparative examples were made into samples according to the standard ISO604: 2002, and tested using an elastic impactor produced by Guangzhou Biaogeda, with the impact drop weight being ASTM100 (2 pounds) and the energy being 5.778 KJ. The surface damage of the samples was recorded, and the results are shown in Table 3.
[0078] Table 3
[0079]
[0080] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the impact-resistant polyurethane material prepared by the present invention has good impact resistance.
[0081] By comparison, the impact resistance of Examples 1 to 3 is better than that of Comparative Examples 1 and 2, indicating that the mechanical strength of silica itself can give polyurethane a certain impact resistance; the long polycaprolactone chain generated by the polymerization of 6-caprolactone on the surface of silica nanosheets can make the silica nanosheets evenly dispersed in the polyurethane and reduce agglomeration; when subjected to external force impact, the long organic chain of polycaprolactone can be deformed, thereby absorbing energy and improving impact strength; the modified polyurethane, modified silica nanosheets, and bismaleimide are blended and cross-linked and cured to obtain an impact-resistant polyurethane material, and the furanyl and maleimide contained in the aromatic rotaxane of the modified polyurethane main chain column undergo Diels-Alder reaction to generate dynamically reversible chemical bonds. Due to the presence of polyrotaxane, the cross-linking points generated by furan maleimide can slide on the polyurethane main chain when subjected to external force impact, providing an efficient energy dissipation mechanism to disperse the impact force and thus give polyurethane impact resistance.
[0082] Test Example 4
[0083] Antimicrobial performance testing
[0084] Test method: The impact-resistant polyurethane materials prepared in Examples 1-3 and Comparative Examples 1-3 were prepared into 6 mm circular slices; the circular slices were placed on an agar medium coated with bacterial solution, inverted in a constant temperature incubator at 37°C for culture, and taken out after one day to measure and record the diameter of the antibacterial zone. Staphylococcus aureus and Escherichia coli were selected for the bacterial solution. The larger the diameter, the better the antibacterial performance. The results are shown in Table 4.
[0085] Table 4
[0086]
[0087] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 4, it can be found that the impact-resistant polyurethane material prepared by the present invention has good antibacterial properties.
[0088] By comparison, the antibacterial properties of Examples 1 to 3 are better than those of Comparative Examples 1 and 3, indicating that 1-(2-bromoethoxy)-4-methoxybenzene and p-phenylenedimethyl ether are reacted to form a columnar aromatic hydrocarbon containing a monobrominated functional group, the monobrominated functional group reacts with the hydroxyl group of (4-hydroxyphenyl)diphenylphosphine, and then reacts with the bromine on 2-(2-bromoethyl)furan to generate a modified columnar aromatic hydrocarbon containing a quaternary phosphonium salt and a furanyl group, and the quaternary phosphonium salt can impart certain antibacterial properties to the polyurethane material.
[0089] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An impact-resistant polyurethane material, characterized in that: The impact-resistant polyurethane material is prepared by cross-linking and curing modified polyurethane, modified silicon dioxide nanosheets, and bismaleimide; The modified polyurethane is a pseudo-polyrotaxane polyurethane obtained by polymerization of isophorone diisocyanate, polytetramethylene furan ether diol and pseudo-polyrotaxane, and is terminated with aminopropylheptyl-cage polysilsesquioxane; the pseudo-polyrotaxane is obtained by reaction of polyethylene glycol and modified pillar aromatic hydrocarbon monomer; the modified pillar aromatic hydrocarbon monomer is obtained by reaction of 1-(2-bromoethoxy)-4-methoxybenzene and p-phenylene dimethyl ether to obtain monobromoethoxy pillar aromatic hydrocarbon, which is then reacted with (4-hydroxyphenyl) diphenylphosphine to obtain a modified pillar aromatic hydrocarbon precursor, which is then reacted with 2-(2-bromoethyl) furan; The modified silicon dioxide nanosheet is obtained by reacting amino silicon dioxide nanosheet with glycidol to obtain hydroxylated silicon dioxide nanosheet, which initiates the ring-opening polymerization of 6-caprolactone, and then reacts with succinic anhydride.
2. A method for preparing an impact-resistant polyurethane material, characterized in that: The method comprises the following preparation steps: (1) Monobromoethoxy pillar aromatic hydrocarbon, (4-hydroxyphenyl) diphenylphosphine, potassium carbonate, tetrabutylammonium bromide and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.27-0.3):(0.24-0.3):(0.03-0.05):(20-30), refluxed at 80°C for 4-6h, and the N,N-dimethylformamide is removed by vacuum rotary evaporation to obtain a modified pillar aromatic hydrocarbon precursor; (2) uniformly mixing the modified pillar aromatic hydrocarbon precursor, 2-(2-bromoethyl) furan, triethylamine and tetrahydrofuran in a mass ratio of 1:(0.6-0.7):(0.03-0.05):(20-30), reacting at 40-50°C for 4-6h, and removing tetrahydrofuran by vacuum rotary evaporation to obtain the modified pillar aromatic hydrocarbon monomer; (3) Mix the modified pillar aromatic monomer, polyethylene glycol and pure water in a mass ratio of 1:(0.5-0.7):(80-100), stir at 80°C for 1 hour, stirring at a speed of 500-600 r / min, cool to room temperature, continue stirring for 46-48 hours, filter and wash with pure water for 3-4 times, and dry at 100°C for 2-3 hours to obtain a pseudopolyrotaxane; (4) At 80°C, isophorone diisocyanate, polytetramethylene glycol, pseudopolyrotaxane, dibutyltin dilaurate, and toluene are mixed in a mass ratio of 1:(2-3):(0.1-0.2):(0.03-0.05):(20-30) for 1-2 h, and n-hexane 3-4 times the volume of toluene is added, filtered, and dried at 50°C for 22-24 h to obtain a pseudopolyrotaxane polyurethane; (5) Mixing the pseudopolyrotaxane polyurethane, aminopropylheptyl-cage polysilsesquioxane and ethanol in a mass ratio of 1:(0.5-0.7):(20-30), stirring at 80°C for 5-6 hours at a stirring speed of 300-400 r / min, adding n-hexane 3-4 times the volume of ethanol, filtering and drying at 50°C for 22-24 hours to obtain a modified polyurethane; (6) Under nitrogen protection, polycaprolactone functionalized silica nanosheets, succinic anhydride, 4-dimethylaminopyridine, and toluene are mixed in a mass ratio of 1:(0.8-1):(0.8-1):(50-60), ultrasonicated at 40 Hz for 20 min, heated to 50-60 °C, reacted for 22-24 h, filtered, and dried at 60 °C for 6-8 h to obtain modified silica nanosheets; (7) The modified polyurethane, modified silica nanosheets and tetrahydrofuran were mixed in a mass ratio of 1: (0.1-0.15): (30-40), and ultrasonically dispersed for 60 min. 1%-3% of bismaleimide by mass of the modified polyurethane was added, stirred for 3-5 min, poured into a polytetrafluoroethylene mold, and dried in an oven at 80 °C for 48 h to obtain an impact-resistant polyurethane material.
3. The method for preparing an impact-resistant polyurethane material according to claim 2, characterized in that: The preparation method of monobromoethoxy pillar aromatics in step (1) is as follows: 1-(2-bromoethoxy)-4-methoxybenzene and terephthalate are mixed in a molar ratio of 1:4, and then added to 1,2-dichloroethane with a mass of 50-60 times that of terephthalate; under nitrogen protection, 6 times the molar amount of 1-(2-bromoethoxy)-4-methoxybenzene is added with polyformaldehyde, wherein the molar amount of polyformaldehyde refers to the molar amount of formaldehyde produced by the decomposition of polyformaldehyde; then, 1.5 times the mass of 1-(2-bromoethoxy)-4-methoxy is added with boron trifluoride etherate; the mixture is stirred at room temperature for 3-4 hours, and 1,2-dichloroethane is removed by rotary evaporation to obtain monobromoethoxy pillar aromatics.
4. The method for preparing an impact-resistant polyurethane material according to claim 2, characterized in that: The preparation method of the polycaprolactone functionalized silica nanosheets in step (6) is as follows: at room temperature, tetraethyl orthosilicate, ethyl acetate and 0.014M sodium hydroxide solution are stirred at a volume ratio of 1:1:100 for 3-4 hours, γ-aminopropyltriethoxysilane (0.2-0.3 times the volume of tetraethyl orthosilicate) is added, stirred for 5-6 hours, heated to 80-90°C for reaction for 1-2 hours, filtered and washed with pure water for 3-4 times, and dried at 50-60°C for 2-3 hours to obtain amino-functionalized silica nanosheets; and the amino-functionalized silica nanosheets are prepared under nitrogen protection. Silica nanosheets and propylene oxide are mixed uniformly in a mass ratio of 1:(20-30), reacted at 45-50°C for 24 hours, filtered and washed with pure water, and dried at 60°C for 6-8 hours to obtain hydroxylated silica nanosheets; hydroxylated silica nanosheets, 6-caprolactone and stannous isooctanoate are mixed in a mass ratio of 1:(8-10):0.01, heated to 130°C under nitrogen protection, reacted for 5-7 hours, filtered, washed with dichloromethane for 3-4 hours, and dried at 60°C for 6-8 hours to obtain polycaprolactone functionalized silica nanosheets.
5. The method for preparing an impact-resistant polyurethane material according to claim 2, characterized in that: The molecular weight of the polyethylene glycol in step (3) is 2000.
6. The method for preparing an impact-resistant polyurethane material according to claim 2, characterized in that: The molecular weight of the polytetrahydrofuran ether diol in step (4) is 2000.
